Relation between Phenomenological Features of Perception and Semantics of Singular Terms in the Context of Taste and Desire Attitudes - M. V. Shkabrova (Дискурс)
Introduction. The study of the semantics of singular terms, that is, such expressions of language that are used to designate a single concrete object, which, first of all, can be sensibly perceived and be a component of our practice in the physical sense, has been going on for several decades. But, according to the author, the essence of singular terms still needs to be clarified in many ways. Does analysis require the meaning of singular terms for tools outside the semantics? If so, what tools should be used? We would like to outline some considerations that may help in answering these questions.Methodology and sources. A considerable number of works by famous researchers of the language are devoted to the disclosure and description of possible approaches to the problems of using singular terms (see, for example, the works of B. Russell, M. Cresswell, Z. Vendler, D. Ninan, M. Schwager, etc.). This article attempts to expand the methodology with phenomenological analysis and description, what explain the citation of M. Merleau-Ponty, A. Schutz, E. Husserl, N.V. Motroshilova, and others.Results and discussion. On the one hand, we classify various linguistic units as singular terms, distinguished according to the specificity that their use has. On the other hand, endowing singular terms with a special status, we are forced to ask ourselves about the prerequisites for the «genesis» of such terms. The work demonstrated the necessity and effectiveness of the phenomenological method, which performs the propaedeutic and explanatory functions in relation to the semantic analysis of singular terms itself.  The reason for this is the close connection between the natural language and the sensory world as a given, which, as the research has shown, cannot be ignored.Conclusion. The closedness of semantics in itself limits the possibilities of analyzing a natural language, in connection with which it seems to us quite clear the actual need to turn to phenomenology. We tried to illustrate the importance of considering the genetic aspects of the use of singular terms and the relationship of their pre-linguistic genesis with the uniqueness of the status of these linguistic units. Therefore, we have good reasons to turn to the phenomenological description of perception and to assert its conceptual connection with the semantics of singular terms.